Constructing two-level nonlinear mixed-effects crown width models for Moso bamboo in China - Zhou, Xiao; Li, Zhen; Liu, Liyang; Sharma, Ram P.; Guan, Fengying; Fan, Shaohui (Frontiers in Plant Science, 2023)
Bamboo crown width (CW) can be used as a reliable index for evaluation of the health and vitality of bamboo, light capture ability of bamboo forest and carbon fixation efficiency. CW can be used as one of the important predictors of the forest growth and yield prediction models. Based on the fit statistics produced from the fitting of the eight basic growth functions using data from 1374 Phyllostachys pubescens in Yixing, Jiangsu Province in China, this study identified the best function (Logistic function) suitable for construction of the two-level mixed-effects (NLME) CW model with the forest block-and sample plot-level effects included as random effects. The effects of different strategies for prior measurement of a response variable and the prediction of the random effects were evaluated. The model with diameter at breast height (DBH), height to crown base (HCB), arithmetic mean diameter at breast height (MDBH), and height (H) used as predictor variables shows the attractive fit statistics. This model was further improved by introducing the random effects at two-levels. Results show the positive correlation of CW with HCB and DBH, and negative correlation with H. The smallest two bamboos per sample plot used for estimating random effects of NLME model provided a good compromise among the measurement cost, model efficiency and prediction accuracy. Presented NLME CW model may provide the guidance for effective management and carbon estimation of bamboo forests.